Dendritic Cell-Based Immunotherapy for Glioma: Multiple Regimens and Implications in Clinical Trials - Mineharu, Yohei (The Japan Neurosurgical Society, 2013)
High grade glioma is a highly invasive brain tumor and recurrence is almost inevitable, even after radical resection of the tumor mass. Cytotoxic immune responses and immunological memory induced by immunotherapy might prevent tumor recurrence. Dendritic cells (DCs) are professional antigen-presenting cells of the innate immune system with the potential to generate robust antigen-specific T cell immune responses. DC-based immunotherapeutic strategies have been intensively studied in both preclinical and clinical settings. Although advances have been made in the experimental use of DCs, there are still considerable challenges that need to be addressed for clinical translation. In this review, we describe the variability of regimens currently available for DC-based immunotherapy and then review strategies to optimize DC therapeutic efficacy against glioma.